1990
DOI: 10.1177/0887302x9000800206
|View full text |Cite
|
Sign up to set email alerts
|

Body Cathexis and Satisfaction with Fit of Apparel

Abstract: Apparel as the product of standard sizing is reflected in female evaluation of self and body, i.e., body cathexis. This study focused upon body cathexis and the perceptions offit of clothing of 107 female consumers. Responses were measured on three scales: (1) satisfaction with fit of apparel at upper, lower, and total body; (2) satisfaction with fit at specific body sites; and (3) a body cathexis scale developed by Rosen and Ross. Analysis of data indicated satisfaction with overall fit at lower body was less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 5 publications
8
175
1
7
Order By: Relevance
“…For these overweight children, poor-fitting clothing, which led to body exposure or the experience of having to custom-order their clothing, sometimes negatively impacted their motivation or desire to participate in physical activity and/or led to a description of their "fat" body parts in a negative fashion. Previous research has looked at adults who perceive their clothing as ill-fitting and found they generate negative feelings about their bodies (LaBat and Delong 1990). This research supports the importance of garment fit to individuals' psychological health across the lifespan.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…For these overweight children, poor-fitting clothing, which led to body exposure or the experience of having to custom-order their clothing, sometimes negatively impacted their motivation or desire to participate in physical activity and/or led to a description of their "fat" body parts in a negative fashion. Previous research has looked at adults who perceive their clothing as ill-fitting and found they generate negative feelings about their bodies (LaBat and Delong 1990). This research supports the importance of garment fit to individuals' psychological health across the lifespan.…”
Section: Discussionsupporting
confidence: 67%
“…Finding garments that fit well was also a frequent problem for adults of different body shapes and sizes (Liechty et al 2009). Adult consumers often blame their bodies instead of the garment when ready-to-wear garments fit poorly (LaBat and DeLong 1990). LaBat and DeLong (1990) found that adults who perceive their clothing as fitting poorly often generate negative feelings about their bodies.…”
Section: Clothing Physical Activity and Overweight Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…바디 이미지는 의복으로 높일 수 있으며, 의 복의 맞음새(fit)와 깊은 관계를 갖는다 (LaBat and DeLong, 1990). 바디 이미지에서 의복의 맞음새 효과는 다양한 체격 을 가진 사람들에 따라 다르게 나타날 수 있다.…”
Section: 연구배경unclassified
“…the abdomen becomes more prominent, the seat flattens, and there is a forward tilt of the head and shoulders (Chumlea et al 1984;Goldsberry et al 1996;Labat and Delong 1990;Reich and Goldsberry 1993;Rosenbald-Walin and Karlsson 1996). Khon (1996) highlighted the importance of providing well-fitting clothing for the older population because of their age-related body changes.…”
mentioning
confidence: 99%